(untitled) (Psychology Travelogs, 2023)
The article reveals the relevance of the problem of stress resistance as a component of self-care for mental health and the health of a specialist in the socio-economic profile. A theoretical analysis of the works of Ukrainian psychologists-scientists on the problem of stress, stress resistance, emotional stability of specialists, health preservation and self-preservation was carried out. The importance of increasing the level of stress resistance and emotional stability of human-to-human workers in order to improve their efficiency and correctness in solving professional tasks, minimize work stress and improve their mental state is described. The importance of the introduction of health-preserving technologies, educational, correctional and educational measures for self-healing and self-preservation of mental health by specialists in the socio-economic profile has been studied. The essence of the concepts: stress, stress resistance, emotional stability, emotional burnout, mental health, self-preservation and health-preserving technologies are clarified and described. It was determined that stress resistance and emotional stability are important components of a specialist’s mental health, because in modern conditions, socio-economic workers face various distresses at work, deterioration of working conditions, and psychosomatic consequences of stress. The focuses on the influence of the emotional factor of stress on the health of a socio-economic specialist. It was determined that stress resistance and emotional stability are directly proportional to the quality of a specialist’s mental health and his professional activity. The concepts of stress resistance and emotional stability as components of self-preservation are considered in detail. The results of an empirical study of the level of stress resistance and emotional stability according to the methods developed highlighted. According to the results of the study, it was determined that the average level of stress resistance and emotional stability prevails among specialists of the socionomic profile, which indicates the presence of problems with the quality of mental health and the need for self-preservation. We see the prospect of further research in the implementation and development of health-preserving technologies, self-healing and self-preservation trainings in institutions for training specialists in the socio-economic profile.